The master plan Himmler's scholars and the Holocaust - Pringle, Heather Anne, 1952 (Hyperion, 2006)
In 1935, Heinrich Himmler established a Nazi research institute called The Ahnenerbe, whose mission was to search around the world for proof of ancient Aryan conquests. But history was not their most important focus--rather, the Ahnenerbe was an essential part of the plan for the Final Solution. The findings were used to convince armies of SS men that they were entitled to slaughter Jews and other groups. Himmler also hoped to use the research as a blueprint for the breeding of a new Europe in a racially purer mold. This book, based on original research, including previously ignored archival material and interviews with living members of the institute, is an exposé of the work of German scientists and scholars who allowed their research to be warped to justify extermination, and who directly participated in the slaughter--many of whom resumed their academic positions at war's end.